Exploring a 'plug and play' smart home system for mobile user - Mantoro, Teddy; Ayu, Media Anugerah (s.n, 2012)
The wireless nodes will minimize the mess of wiring and it is hoped that the system can be optimized to a point where it becomes ‘plug and play’ and can be set up in anyone’s home. Sensors attached to the nodes of this system will assist in sending alerts to the home owner or relevant authorities if any security issues or hazards such as a fire etc. are detected. Sensors would also communicate amongst each other to enhance the relaxation of a person in the home by minimizing and improving an occupant’s physical interaction with the home.